2014
DOI: 10.18632/oncotarget.2008
|View full text |Cite
|
Sign up to set email alerts
|

Selenocysteine derivative overcomes TRAIL resistance in melanoma cells: evidence for ROS-dependent synergism and signaling crosstalk

Abstract: Tumor necrosis factor–related apoptosis-inducing ligand (TRAIL), as one of the most promising targeted drug for new cancer therapeutics, is limited in clinical application by the evolution of resistance in many cancer cell lines, especially in malignant melanoma. Thus, it is urgently needed to identify chemosensitizers to enhance the apoptotic inducing efficacy of TRAIL and overcome resistance of malignant melanoma cells. Herein, we reported that 3,3′-diselenodipropionic acid (DSeA), a Selenocysteine derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Study has suggested that the combination treatment of metal-based agent (cisplatin) and TRAIL have the potential of providing a novel strategy for improving the chemotherapeutic efficacy in TNBC patients 39 . Recently, we also showed that, pretreatment of cells with organic selenium compound could enhance the apoptosis-inducing efficacy of TRAIL in A375 cells through induction of ROS-dependent Akt dephosphorylation 40 . Results in the present work showed that RuPOP effectively suppressed FAK-mediated ERK and Akt phosphorylation after 24 h treatment in MDA-MB-231 cells ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Study has suggested that the combination treatment of metal-based agent (cisplatin) and TRAIL have the potential of providing a novel strategy for improving the chemotherapeutic efficacy in TNBC patients 39 . Recently, we also showed that, pretreatment of cells with organic selenium compound could enhance the apoptosis-inducing efficacy of TRAIL in A375 cells through induction of ROS-dependent Akt dephosphorylation 40 . Results in the present work showed that RuPOP effectively suppressed FAK-mediated ERK and Akt phosphorylation after 24 h treatment in MDA-MB-231 cells ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The treated U251 cells were washed with PBS and then incubated with cell lysis buffer overnight at À20 C. Protein electrophoresis and blotting were performed as described in our previous methods (Cao et al 2014). Briefly, SDS-PAGE was done in 12% Tricine gels loading 30 lg of cell lysates per lane.…”
Section: Western Blottingmentioning
confidence: 99%
“…Considering the development of drug resistance, patients have to receive high doses of cisplatin, thereby leading to undesirable side effects (Sprauten et al 2012). Chemo-sensitization is also an effective strategy to overcome drug resistance and reduce adverse effects (Cao et al 2014;Zhang et al 2014;Gong et al 2018). Thus, the development of novel chemosensitizers to enhance the anticancer efficacy of cisplatin-based therapy is important in clinical cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3,3′-diselenodipropionic acid (DSePA), a stable and water-soluble diselenide, exhibits robust protective potential against cell damage or apoptosis in many fields [15,16]. Due to its high efficacy and less toxicity, DSePA has attracted much attention of many researchers, especially for its antioxidant effect [17]. Antioxidative stress currently was accepted as the critical cellular event for the protective action of DSePA.…”
Section: Introductionmentioning
confidence: 99%